2014
DOI: 10.1161/hypertensionaha.113.02504
|View full text |Cite
|
Sign up to set email alerts
|

Diastrophic Dysplasia Sulfate Transporter (SLC26A2) Is Expressed in the Adrenal Cortex and Regulates Aldosterone Secretion

Abstract: A rterial hypertension is a major cardiovascular risk factor that affects ≈30% to 60% of the population depending on the age group concerned.1 Pathogenic mechanisms underlying so-called essential hypertension are complex and include genetic and environmental, and vascular and hormonal factors. In community-based samples, increased aldosterone levels within the physiological range predispose to the development of high blood pressure. 2,3 On the far side of the spectrum, primary aldosteronism (PA), a form of en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Sexual dimorphism in the mouse adrenal gland is well established, with clear sex differences in gene expression observed within the adrenal gland (86). Several previous mouse models of adrenal dysfunction have had varying results between the sexes (49,67,68,70,75,87). This further argues for a sex-dependent mechanism of adrenal regulation, possibly driven by androgens or estrogens.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual dimorphism in the mouse adrenal gland is well established, with clear sex differences in gene expression observed within the adrenal gland (86). Several previous mouse models of adrenal dysfunction have had varying results between the sexes (49,67,68,70,75,87). This further argues for a sex-dependent mechanism of adrenal regulation, possibly driven by androgens or estrogens.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variants in the REN gene were not Review associated with PRA or PRC, nor were SNPs at the CYP11B2 locus associated with circulating aldosterone concentrations. An independent analysis of the data on 1786 subjects of the Cooperative Health Research in the Region of Augsburg F4 cohort (KORA) had previously shown a highly significant genome-wide association of SNPs at chromosome 5q32 with the ARR [42]. Among the genes contained in the interval, the SLC26A2 locus codes for solute carrier family 26 member 2, a protein with known transport activity for sulfate and other cations.…”
Section: Genetic Contribution To Aldosterone and Renin Levels And Posmentioning
confidence: 99%
“…Regarding potential germline variants, whether genome-wide association studies (GWAS) or next-generation sequencing studies would be helpful remains to be determined. Prior GWAS studies have focused on aldosterone to renin ratio in a population-based cohort (not PA) [47] or candidate gene association with aldosterone levels [48].…”
Section: The Unknown Unknownsmentioning
confidence: 99%